2019
DOI: 10.1371/journal.pone.0213696
|View full text |Cite
|
Sign up to set email alerts
|

Transspinal stimulation increases motoneuron output of multiple segments in human spinal cord injury

Abstract: Targeted neuromodulation strategies that strengthen neuronal activity are in great need for restoring sensorimotor function after chronic spinal cord injury (SCI). In this study, we established changes in the motoneuron output of individuals with and without SCI after repeated noninvasive transspinal stimulation at rest over the thoracolumbar enlargement, the spinal location of leg motor circuits. Cases of motor incomplete and complete SCI were included to delineate potential differences when corticospinal mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(75 citation statements)
references
References 64 publications
(61 reference statements)
9
66
0
Order By: Relevance
“…Individuals with motor complete SCI were included in order to assess potential changes in presence of minimal descending inputs. Both SCI and healthy control subjects participated in a previous study [10], and are identified here with the same code.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Individuals with motor complete SCI were included in order to assess potential changes in presence of minimal descending inputs. Both SCI and healthy control subjects participated in a previous study [10], and are identified here with the same code.…”
Section: Methodsmentioning
confidence: 99%
“…A single reusable self-adhered cathode electrode (10.2 × 5.1 cm 2 , Uni-Patch, Massachusetts, USA) was placed at T10 equally spaced along the vertebrae ending at L1-2. Two interconnected electrodes (anode, same type as the cathode) were placed on either side of the abdominal muscles or iliac crests depending on each subject’s reported level of comfort or if stimulation caused bladder discomfort [7,8,10,17,18]. Stimulation was delivered by a constant current stimulator (DS7A or DS7AH, Digitimer, Welwyn Garden City, UK) that was triggered by Spike 2 scripts (Cambridge Electronics Design Ltd., Cambridge, UK).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations